Adubação mineral em cultivares de batata: produtividade, qualidade e sistema integrado de diagnose e recomendação DRIS - Oliveira, Roberta Camargos de (2017)
Potatoes are a food rich in health-friendly nutrients and compounds. It offers affordable price, high acceptability and versatility, with increasing demands over the decades. Among the management factors of the crop, the supply of nutrients to the plants contributes decisively to its productivity and quality. This causes farmers to apply high doses, often beyond the absorption capacity of plants, which increases production costs and risks of environmental contamination. Therefore, the objective of this study was to evaluate the influence of nitrogen fertilizer (N), phosphate (P2O5) and potassium (KC1) fertilizer rates on the productivity of potato tubers of the cultivars Ágata and Atlantic. Three concurrent experiments were carried out, one for each nutrient: nitrogen (N), phosphorus (P) and potassium (K). The cultivar Agata was cultivated in Unai-MG and Mucugê-BA and the Atlantic was cultivated in Unai-MG. The experimental design was a randomized block design with four replications. Doses of N: 0, 30, 70, 120 and 280 kg ha"1 of N were studied, as well as doses of P: 0, 150, 300, 600 e 900 kg ha'1 of P2O5 and doses of K: 0, 70, 110, 220 e 450 kg ha"1 of K2O. In each experiment there was only one nutrient variation, with the other doses fixed at the recommended dose (120, 480 and 220 kg ha"1 of N, P2O5 and K2O, respectively). Productivity of special and total potato tubers responded to N rates in all cultivars and sites. The maximum doses varied between 138 and 194 kg ha"1 of N in region with high and low CTC soils, respectively. The maximum doses estimated for total productivity in Atlantic-MG, Ágata-MG and Ágata-BA were respectively: 606, 730 and 535 kg ha"1 of P2O5, with productivities of 38, 47.6 and 59.7 t ha"1, respectively. The cultivar Atlantic-MG did not respond to the increase of potassium fertilization, with productivity between 32.3 and 37 t ha"1. The cultivars Ágata-MG and Ágata-BA responded up to the estimated dose of 225 and 166 kg ha"1 of K2O with maximum productivity of 53.9 and 56.2 t ha"1, respectively. The qualitative factors presented small differences between cultivars and rates of all evaluated nutrients. Therefore, the fertilization interferes more substantially in the amount produced. Regarding the adoption of the DRIS Recommendation and Diagnosis System, it was observed that the most limiting nutrients in the areas of high and low productivity, respectively, presented the following order for the Ágata-MG cultivar: Cu> P> B> Ca> Fe > Mn> N> Zn> Mg> K> S and P> Ca> Cu> B> Fe> Mg> N = K = S = Mn = Zn; Agata-BA: Mg> Ca> B> Cu> N> Fe> Zn> P> Mn> K and B> Cu> Mg> Fe> P> N> Mn> Ca> K > S> Zn; Atlantic-MG: Mg> K> N> Fe> Cu> B> S> P> Mn> Ca> Zn and P> Mg> Cu> N> S> Mn> Fe> Ca> Zn> K. The qualitative factors of the evaluated potato presented small differences between cultivars as well as between the doses of all nutrients evaluated. Therefore, the fertilization interferes more substantially in the quantity produced.